Peer Support to Enhance Social and Emotional Self-Management Following Acquired Brain Injury Rehabilitation: Design of a Pre–post Study With Process Evaluation - Baumgartner-Dupuits, Milou; Sep, Simone J. S.; Verbunt, Jeanine; Bosma, Hans; van Eijk, Jacques (Frontiers in Neurology, 2021)
Background: Specialized rehabilitation following acquired brain injury provides intensive multidisciplinary treatment to individuals with complex disabilities to optimize recovery and support a safe transition to the community. Post specialist rehabilitation, patients and caregivers have reported a need for support . We present the design of an implementation study to evaluate a new self-management support service for individuals with acquired brain injury and their caregivers. Methods: This is a pre-post intervention study with a mixed-method design. The study population comprises individuals aged ≥18 years with acquired brain injury living independently following specialized rehabilitation in the Southern part of the Netherlands. All participants receive a post-rehabilitation support service. The support service consists of several house visits by a peer support volunteer in the first weeks after specialized rehabilitation treatment. The peer support volunteers are trained according to an adapted version of the previously developed Self-Management Support (SMS) programme. The SMS programme is directed at improving social and emotional self-management. Patient outcomes are assessed by questionnaire pre-, directly post- and 6 months post-intervention. The primary patient outcome measure is self-efficacy. Secondary outcomes are perceived autonomy, quality of life and psychological wellbeing. A process evaluation will be performed to gain insight into barriers and facilitators to the implementation of peer-led SMS by combining both quantitative, questionnaire data and qualitative data derived by use of focus groups with peer supporters and patients. In a workshop with relevant stakeholders possibilities for dissemination and sustainability will be explored. Discussion: This paper describes the design of a practice-based study on feasibility, barriers and facilitators to the implementation of a home-based, peer-led self-management support intervention for patients with acquired brain injury. We will quantitatively and qualitatively evaluate the change in relevant patient outcomes pre- and post-intervention, and the barriers and facilitators related to the implementation of the intervention. The final stage of the study aims to facilitate deployment and utilization of the intervention, following a positive evaluation.